Plasma-assisted CO2 conversion in a gliding arc discharge: Improving performance by optimizing the reactor design. (January 2019) - Li, Li; Zhang, Hao; Li, Xiaodong; Kong, Xiangzhi; Xu, Ruiyang; Tay, Kangrou; Tu, Xin
Graphical abstract: Highlights: A gliding arc discharge (GAD) is investigated for CO2 dissociation. The effect of feed flow rate on CO2 conversion exhibit two patterns. High temperature can stimulate the recombination reaction of CO and O. GAD shows advantages in energy efficiency and processing capacity. Quadrangular cover is proved to have a better space utilization and performance. Abstract: In this paper, a gliding arc discharge (GAD) is investigated for CO2 decomposition, with particular efforts directed toward improving the performance by optimizing the reactor design. The effects of various parameters, e.g., gas flow rate, configuration of the injector nozzle, and structure of the quartz cover, on the CO2 conversion and energy efficiency are investigated. The results indicate that the variation profiles of CO2 conversion upon rising flow rate can be clearly be divided into two patterns: Pattern A with outlet gas temperature > 440 °C and Pattern B with outlet gas temperature < 440 °C. The CO2 conversion rises in Pattern A but decreases in Pattern B with the increase in flow rate. The relatively high temperature in Pattern A is negatively correlated with CO2 conversion because it can stimulate the recombination of CO and O, which leads to the increase in CO2 conversion with increasing flow rate (and decreasing gas temperature). A smaller injector nozzle diameter (1.0 mm) exhibits a better performance in terms of both CO2 conversion and energy efficiency under most of the conditions studied, and a longer distance between the injector nozzle and electrodes is beneficial to the CO2 conversion at relatively high flow rates (≥ 4 L/min). A quadrangular reactor cover was proved to have a better space utilization and a higher fraction of gas treatment by plasma, which can ensure a more adequate contact between the injected gas and plasma, and thus a better performance. The optimum conditions are: flow rate = 3 L/min, nozzle diameter = 1.0 mm, distance between injector nozzle and electrodes = 5.0 mm, and a quadrangular cover, under which CO2 conversion and energy efficiency up to 11.1% and 20.7% can be achieved. Compared to other typical non-thermal plasmas, such as dielectric barrier discharge and corona discharge, GAD shows a significantly higher energy efficiency along with a flow rate that is an order of magnitude higher.